Droop control technique for equal power sharing in islanded microgrid - A. W. N. Husna; M. A. Roslan; M. H. Mat (Institute of Advanced Engineering and Science, 2019)
This paper presents a droop control technique for equal power sharing in islanded microgrid. In this study, the proposed controller is based on the frequency droop method, is applied to a robust droop controller in parallel connected inverters. The previous robust droop controller deals with voltage droop method. A modification has been formed against this controller by adding a fuzzy logic controller with the frequency droop method. The only sharing error which is concentrated in this paper is the error in sharing the rated frequency among the inverters. By adapting fuzzy in the robust droop, it tries to eliminate the frequency error, hence that the frequency reference of the inverters keeps maintain at 50Hz. A derivation of generalized models of a single-phase parallel-connected inverter system is shown. The simulation results show that the proposed controller with FLC is able to improve the stability of frequency reference and the performance of power sharing between the inverters under the inductive line impedance.